ShotBlocker versus cryotherapy for reducing pain and anxiety associated with subcutaneous injection - Hafez Dalia Masoud Elsaid; Ali Wafaa Gameel Mohammed (Sciendo, 2023)
To determine and compare the abilities of ShotBlocker and cryotherapy for reducing pain and anxiety associated with subcutaneous injections. Subcutaneous injection has been used excessively for continuous, low-dose administration of drugs. Considering that these drugs may require prolonged administration, new devices and methods of injection are needed to decrease pain and anxiety associated with repeated drug injections.